‘Polishing the Apple’: The Systematic Eradication of ‘Otherness’ from the New York Crowd - Darren Richard Carlaw (Conserveries Mémorielles)
This article recognises Manhattan’s current precarious state as it seeks to evict ‘outsiders’ from its shores via a combined process of surveillance and gentrification. This ongoing filtering process will have a direct impact on the multiplicity of its crowds, as the presence and history of the ‘outsider’ is rapidly eradicated. Manhattan has been a partitioned space since its early beginnings as a metropolis. The rigid grid system was an attempt to impose order on a disorderly space. I examine the manner in which a potential for disorder has always been inherent within the grid, and how the current efforts to stem all forms of disorder at street level threatens Manhattan’s existence as a creative centre. I further examine the street as a performance space. The city’s density and complex network of social boundaries dictate a definite sense of place, in terms of insider and outsidership. In such a space, the performance of identity becomes an essential survival method for the walker when passing through multiple urban divides. I seek to critically reassess how strategies of social transgression employed by Manhattan’s community of excluded ‘outsiders’, such as ‘passing’, border crossing and flânerie have been appropriated and/or utilised by the State. As pedestrians come under increasingly heavy surveillance, I consider the manner in which the city’s nomads have taken refuge beneath the streets. My analysis of current trends portends the creation of an obedient, sterile cityspace where ‘outsidership’ itself is no more than a mere performance.